Flood Inundation Prediction of Logung River due to the Break of Logung Dam - Listyo Rini Ekaningtyas (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
The construction of Logung Dam in Kudus Regency is aimed to reduce the inundation area at downstream of Logung River, particularly during the rainy season. Besides, the potential water of Logung Dam is used for for irrigation and non-irrigation services. In order to mitigate the flood disaster that may arise in the downstream area, various preparedness should be established including the identification of flood hazard characteristics that may be caused by the break of the Logung Dam. This paper presents the results of Logung Dam break analysis using the levee pool routing model and the 2-D channel routing of the HEC-RAS 5.0 Version software. The initial value of breach parameter was calculated using the Froehlich’s equation, and variation of breaking times (1, 2, and 3 hours) were applied to study the generated hydrograph based on the corresponding elevation-storage curve. Furthermore, the simulation of channel routing at downstream of the dam was carried out in three different scenarios based on the bridges condition at downstream of the Logung Dam. Scenario 1 assumed that bridges will be safe enough against flood. Scenario 2 assumed that the bridges would only be safe at flood with return period lower than 20 years, whereas the scenario 3 assumed that bridges would be collapsed due to the flood at design flood with several return periods. The simulation results showed that the Probable Maximum Flood (PMF) with peak discharge of 1,303.60 m3/s did not generate overtopping. The peak discharge through the dam body was 15,022 m3/s at the first 40 minutes. It took 7 hours and 30 minutes to decrease the water level of the reservoir from +95.2 m to +38 m. In scenario 2, the simulation used 20 years return period flood with velocity in cross section before the Bridge RS 3700 was 7.21 m/s and before Bridge RS 6800 was 5.72 m/s. Furthermore, the 2-D simulation results showed that at the near downstream of the Logung Dam, the maximum depth was 55 m and the maximum velocity was 39 m/s. Several prone areas to flood caused by the dam break are the villages at the left side of the downstream Logung River including Bulung Cangkring, Bulung Kulon, Sidomulyo, Pladen and Jekulo village.